Learning Management Of Programmable Logic Controller (PLC) At SMK Muhammadiyah Cepu - Supriyanto, Agus, Dra. Dwi Haryanti, M. Hum, Prof. Dr. Yetty Sardjono, M.Si (2013)
Developments in science and technology has brought new changes in human life. The changes have also brought people into the era of global competition is increasingly fierce. Industry is growing by leaps and bounds since their productivity is supported modern equipment that works automatically, commonly called automation. Seeing this condition we must prepare our students fit the needs of industry, so that the child is really ready to use when it plunged into the world of industry. To be competitive, it is necessary to the management of learning is done in a planned, focused, intensive, effective and efficient in the development process . The objectives of this research is to describe the planning, implementation and evaluation of learning Programmable Logic Controller (PLC) in SMK. The research method used was a qualitative study, because the researcher wanted to describe the learning management Programmable Logic Controller (PLC) in SMK. The study design was ethnography. Data collection based on the source can use primary sources and secondary sources. Sources of data in this study consist of events, informants and documents. Data collection method is observation, interviews, and documentation. Activity in the analysis of data, namely data reduction, the data display, and conclusion drawing / verification. To check the validity of the data, namely: the extension of the observations, increased diligence in research, triangulation, discussions with peers, negative case analysis, member checks Management is expected to help the process of learning activities that take place running smoothly. In this regard, the institution requires a learning management can arrange it. With the aim of learning in school can be run effectively and efficiently. Learning management Programmable Logic Controller succeed if through the learning stages of planning, implementation and evaluation of learning lessons Programmable Logic Controller.